2003
DOI: 10.1097/00004850-200303000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of homovanillic acid and the response to risperidone in first episode untreated acute schizophrenia

Abstract: We have previously reported that risperidone might improve negative symptoms in schizophrenia by influencing noradrenergic neurons. In the present study, we focused on the clinical efficacy and mechanisms of risperidone towards positive symptoms in the acute phase of schizophrenia. Thirty-four patients meeting DSM-IV criteria for schizophrenia and treated with risperidone alone were evaluated regarding their clinical improvement using the Positive and Negative Syndrome Scale (PANSS) before and 2 weeks after ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 18 publications
3
25
2
1
Order By: Relevance
“…In contrast, data from the present study suggest that ΔpHVA may have a predictive value for responsiveness and possibly outcome in individual patients, as has also been suggested by others [31]. …”
Section: Discussionsupporting
confidence: 77%
“…In contrast, data from the present study suggest that ΔpHVA may have a predictive value for responsiveness and possibly outcome in individual patients, as has also been suggested by others [31]. …”
Section: Discussionsupporting
confidence: 77%
“…In vitro and in vivo studies have demonstrated that risperidone is a mixed serotonin (5-HT 2 ) and dopamine (D 2 ) receptor antagonist Leysen et al, 1988). We have reported that risperidone is effective for treating the acute phase of schizophrenia with few extrapyramidal side effects (Yoshimura et al, 2003. Furthermore, we have reported that risperidone is also effective in treating negative symptoms of chronic schizophrenic patients (Yoshimura et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Этому предположению соответствуют дан-ные о значительном (почти двукратное) повышении ак-тивности тромбоцитарной моноаминоксидазы (МАО) у больных с первым эпизодом шизофрении, что свидетель-ствует о нарушении баланса дофамина и серотонина в ЦНС [11,24]. Основные психопатологические проявления у боль-ных шизофренией, в частности с ППЭ, связаны с наруше-ниями моноаминового баланса в префронтальной коре головного мозга [25].…”
Section: результаты и обсуждениеunclassified